PERSEPSI PENGGUNA LRT JABODEBEK STASIUN HARJAMUKTI - Imantaka, Eldwin; Najid; Angkat, Hokbyan R.S. (JMTS: Jurnal Mitra Teknik Sipil, 2024)
Light Rail Transit (LRT) is a type of train that allows people who own private vehicles to switch to mass transportation. The purpose of LRT is to reduce congestion in Jabodebek. Both facilities and services support the use of mass transportation. The purpose of research is see the perceptions users of LRT Jabodebek LRT at Harjamukti Station. This station is a station that has been opened and serves to help people around Cibubur to Jakarta. The Cibubur community has several disadvantages when heading to the Harjamukti LRT station. One of them is the distance between the parking lot and the Harjamukti LRT station. In addition, the limit of public transportation that drops off passengers makes the Harjamukti LRT station still too far away. A survey on the perception of Harjamukti Station LRT users was conducted by distributing questionnaires to 120 people.